2013
DOI: 10.2172/1170502
|View full text |Cite
|
Sign up to set email alerts
|

Glass Property Models and Constraints for Estimating the Glass to be Produced at Hanford by Implementing Current Advanced Glass Formulation Efforts

Abstract: Recent glass formulation and melter testing data have suggested that significant increases in waste loading in high-level waste (HLW) and low-activity waste (LAW) glasses are possible over current system planning estimates. The data (although limited in some cases) were evaluated to determine a set of constraints and models that could be used to estimate the maximum loading of specific waste compositions in glass. It is recommended that these models and constraints be used to estimate the likely HLW and LAW gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(98 citation statements)
references
References 44 publications
1
97
0
Order By: Relevance
“…The conversion occurs in the cold cap, a reacting mass that floats on the surface of molten glass . Together with the waste loading in the glass, the rate of conversion (the rate of melting) is a major factor in the glass production efficiency . It is influenced by the mineralogical form of the glass additives, the particle size of solids, the loading and type of waste, and the melter feed rheology .…”
Section: Introductionmentioning
confidence: 99%
“…The conversion occurs in the cold cap, a reacting mass that floats on the surface of molten glass . Together with the waste loading in the glass, the rate of conversion (the rate of melting) is a major factor in the glass production efficiency . It is influenced by the mineralogical form of the glass additives, the particle size of solids, the loading and type of waste, and the melter feed rheology .…”
Section: Introductionmentioning
confidence: 99%
“…Recent small-scale melter tests with seven representative Hanford LAW glass feeds (simulated waste plus additives) for the WTP showed that the fraction of technetium retained in glass (referred to as retention) varied from 18% to 66% depending on the feed composition [12][13][14]. Although the volatilized 99 Tc can be captured in the off-gas treatment system and recycled to the melter to increase the retention, the recycle stream also contains other volatile components such as sulfur (S), chlorine (Cl), and fluorine (F) that decrease the loading of waste in the glass [17] and, thus, increase the glass volume. Maximizing the incorporation of 99 Tc into glass is desirable also to minimize the fraction that needs to be treated as a secondary waste and disposed in non-glassy waste forms [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Further details about the data sets compiled to form the 747-point database are contained in Table 2.1 of Vienna et al 15 The portion of the database for the example in this article is available as supporting information. This example is used in the rest of the article to illustrate fitting mixture experiment models expressed in terms of DRCs using NLR (ie, NLR-DRC models).…”
Section: An Example For a Waste Glass Mixture Experiments With Drcs mentioning
confidence: 99%